Long-term follow-up of normal and structural heart ventricular tachycardia catheter ablation: real-world experience from a UK tertiary centre. Issue 2 (24th September 2019) - Adlan, Ahmed M; Arujuna, Aruna; Dowd, Rory; Hayat, Sajad; Panikker, Sandeep; Foster, Will; Yusuf, Shamil; Umar, Fraz; Lellouche, Nicolas; Osman, Faizel; Dhanjal, Tarvinder
Abstract : Background: Ventricular tachycardia (VT) is associated with increased morbidity and mortality. There is growing evidence for the effectiveness of catheter ablation in improving outcomes in patients with recurrent VT. Consequently the threshold for referral for VT ablation has fallen over recent years, resulting in increased number of procedures. Objective: To evaluate the effectiveness and safety of VT ablation in a real-world tertiary centre setting. Methods: This is a prospective analysis of all VT ablation cases performed at University Hospital Coventry. Follow-up data were obtained from review of electronic medical records and patient interview. The primary endpoint for normal heart VT was death, cardiovascular hospitalisation and VT recurrence, and for structural heart VT was arrhythmic death, VT storm (>3 episodes within 24 hours) or appropriate shock. Results: Forty-seven patients underwent 53 procedures from January 2012 to January 2018. The mean age ±SD was 57±15 years, 68% were male, 81% were Caucasian and 66% were elective cases. The aetiology of VT included normal heart (49%), ischaemic cardiomyopathy (ICM, 36%), dilated cardiomyopathy (9%), hypertrophic cardiomyopathy (4%) and valvular heart disease (2%). Procedural success occurred in 83%, with six major complications. After a median follow-up of 231 days (lower quartile 133, upper quartile 631), the primary outcome occurred in 28% of patients. There were two non-arrhythmic deaths (4%). At a median follow-up of 193 days (129–468), the primary outcome occurred in 19% of patients with ICM, while VT storm/appropriate shocks occurred in three patients (17%). Conclusions: Our real-world registry confirms that VT ablation is safe, and is associated with high acute procedural success and long-term outcomes comparable with randomised controlled studies.